Diaspora Minangkabau di Malaysia: Biografi Elvis Syefrizal dan Perannya dalam Pelestarian Budaya - Nabilla, Hanna Syafwatul; Syafrizal, Syafrizal (Analisis Sejarah, 2025)
The Minangkabau diaspora in Malaysia reflects a deeply rooted migration tradition shaped by economic, social, and cultural dynamics. This study explores the life journey of Elvis Syefrizal, a Minangkabau migrant who founded the Pustaka Rezeki Harapan bookstore in Kuala Lumpur. Focusing on the motivations behind Minangkabau migration, strategies of adaptation, and efforts to preserve cultural identity abroad, the research adopts a biographical and qualitative approach, drawing on in-depth interviews and literature review. The findings highlight how Elvis Syefrizal actively preserves Minangkabau cultural heritage through social engagement, entrepreneurship, and the intergenerational transmission of traditions within his family and migrant community. His leadership in diaspora organizations further reinforces cultural continuity and solidarity among fellow migrants. This study contributes to the fields of diaspora and migration studies by presenting a localized, human-centered narrative of cultural preservation within voluntary migration. It underscores that migration is not merely a spatial relocation, but a dynamic, ongoing process of cultural negotiation, adaptation, and the maintenance of transnational connections.